La gestión du couple QUESTION-RÉPONSE (Q-R) en situation de communication assistée par un(e) interprete - Apfelbaum, Birgit (Studia Romanica Posnaniensia, 2007)
This paper explores the interactional management of question-answer sequences in interpreter-mediated business encounters and discusses didactic applications for interpreter training. A close analysis of transcripts from authentic audiotaped data reveals how the turn-taking system in the translational mode is particularized to contextual needs, i.e., as talk progresses, the business partners, rather than addressing one another, take turns being ‘bystanders’ as the other one communicates with the interpreter respectively. The interpreter takes and is given responsibilities to make the question-answer sequences work, especially as far as respecting conditional relevances is concerned. This system seems to be fully functional for a professional management of such situations and thus could be used as an analytical tool in training future liaison interpreters.